Diagnostic Testing for Mild Hemophilia A in Patients with Discrepant One-Stage, Two-Stage, and Chromogenic Factor VIII:C Assays - Duncan, Elizabeth M.; Rodgers, Susan E.; McRae, Simon J. (Seminars in Thrombosis and Hemostasis, 2013)
In recent years, there has been greater awareness among hemostasis scientists and clinicians that factor VIII coagulant activity (FVIII:C) measured in certain patients with mild hemophilia A can show different results depending on the assay system. A subgroup of mild hemophilia families have a method-related discrepancy in FVIII:C results, whereby the one-stage clotting assay (FVIII:C-1) is significantly higher than the two-stage clotting assay (FVIII:C-2) or the chromogenic assay (FVIII:C-chr). To identify such patients, the routine laboratory can use automated procedures for the FVIII:C-chr to replace the complex, manual FVIII:C-2 method. Laboratories must employ appropriate quality management to ensure accurate and precise results, especially in the abnormal range. This discrepant phenotype of hemophilia A is seen in up to 40% of mild hemophilia A cases and represents a clinically significant bleeding disorder. A small proportion of these cases have FVIII:C-1 within the normal range and risk a missed diagnosis if the FVIII:C-chr is unavailable. Other patients may be mismanaged if FVIII:C-1 gives an overestimate of FVIII:C and their bleeding risk is consequently underestimated. Affected family members in the discrepant group of patients have a limited range of FVIII (F8) gene missense mutations, causing alterations of the structure of the A1, A2, or A3 domains of FVIII. Therefore, both FVIII:C-chr and F8 gene mutation analysis are recommended to confirm the diagnosis of mild hemophilia A and assist with decisions about the patient's phenotype.
Keywords: factor VIII; hemophilia A; discrepant; assay methods